2023
DOI: 10.1177/01939459231152056
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Care Needs and Related Factors of Lung Transplant Patients at Home

Abstract: The purpose of this study was to explore the relationship among unmet care needs, social support, and anxiety in patients with lung transplantation. We conducted a cross-sectional study; 173 lung transplant patients who met the inclusion criteria completed questionnaires including the Organ Transplant Recipient Care Needs Scale, the Perceived Social Support Scale, and the Anxiety Self-Rating Inventory. Pearson’s correlations and multiple linear regression analyses were used to test the relationship between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This finding suggested that more attention should be given to LTx patients with hospital readmission due to infection. For instance, some interventions involve closely monitoring their condition ( 51 ), implementing effective infection control measures and follow-up strategies ( 52 ), are instrumental in reducing fear of disease progression and improving QOL. Moreover, health education is important in understanding lung infection’s signs and symptoms and evolution which enables patients to seek early treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that more attention should be given to LTx patients with hospital readmission due to infection. For instance, some interventions involve closely monitoring their condition ( 51 ), implementing effective infection control measures and follow-up strategies ( 52 ), are instrumental in reducing fear of disease progression and improving QOL. Moreover, health education is important in understanding lung infection’s signs and symptoms and evolution which enables patients to seek early treatment.…”
Section: Discussionmentioning
confidence: 99%